К расчету проточных частей высоконапорных радиально-осевых обратимых гидромашин - Дранковский, Виктор Эдуардович; Хавренко, Михаил Юрьевич; Шудрик, Александр Леонидович (НТУ "ХПИ", 2016)
Рассмотрена методика аналитического определения очертаний меридиональной проекции рабочего колеса обратимой гидромашины. Проведено сравнение основных геометрических параметров обратимых гидромашин, насосов и гидротурбин. Даны рекомендации для определения всасывающего диаметра вс D , ширины колеса нап b , углов наклона лопасти вс b и нап b и положения всасывающей кромки. Составлена и использована программа для построения очертаний меридиональной проекции рабочего колеса обратимой гидромашины.

In the article an analytical method for determining the shape of the meridional projection of the impeller of the Francis pump-turbine is considered and its modifications are analyzed. A computational algorithm for determining the meridional projection is presented. The dependence of the basic geometrical parameters on the specific speed in the pump mode is given. The ways to determine the height and suction diameter of the impeller are recommended. The choices of the angles on the suction and pressure side of the scapula are substantiated. The cavities for pump-turbine pumps and turbines for various speeds are built. A program for building the meridional projection in the first approximation is created
On calculating flowing parts of high-pressure reversible Francis pump-turbine
Keywords: энергосистема; ГАЭС; рабочее колесо; меридиональная проекция; насос-турбина; PSPP; pump-turbine; flowing part; meridional projection